Cognitively Engaging Activity Is Associated with Greater Cortical and Subcortical Volumes - Seider, Talia R.; Fieo, Robert A.; O’Shea, Andrew; Porges, Eric C.; Woods, Adam J.; Cohen, Ronald A. (Frontiers in Aging Neuroscience, 2016)
As the population ages and dementia becomes a growing healthcare concern, it is increasingly important to identify targets for intervention to delay or attenuate cognitive decline. Research has shown that the most successful interventions aim at altering lifestyle factors. Thus, this study examined how involvement in physical, cognitive, and social activity is related to brain structure in older adults. Sixty-five adults (mean age = 71.4 years, standard deviation = 8.9) received the Community Healthy Activities Model Program for Seniors (CHAMPS), a questionnaire that polls everyday activities in which older adults may be involved, and also underwent structural magnetic resonance imaging. Stepwise regression with backwards selection was used to predict weekly time spent in either social, cognitive, light physical, or heavy physical activity from the volume of one of the cortical or subcortical regions of interest (corrected by intracranial volume) as well as age, education, and gender as control variables. Regressions revealed that more time spent in cognitive activity was associated with greater volumes of all brain regions studied: total cortex (β = .289, p = .014), frontal (β = .276, p = .019), parietal (β = .305, p = .009), temporal (β = .275, p = .020), and occipital (β = .256, p = .030) lobes, and thalamus (β = .310, p = .010), caudate (β = .233, p = .049), hippocampus (β = .286, p = .017), and amygdala (β = .336, p = .004). These effects remained even after accounting for the positive association between cognitive activity and education. No other activity variable was associated with brain volumes. Results indicate that time spent in cognitively engaging activity is associated with greater cortical and subcortical brain volume. Findings suggest that interventions aimed at increasing levels of cognitive activity may delay cognitive consequences of aging and decrease the risk of developing dementia.